High-temperature polyimide dielectric materials for energy storage: theory, design, preparation and properties - Liu, Xue-Jie; Zheng, Ming-Sheng; Chen, George; Dang, Zhi-Min; Zha, Jun-Wei (Energy & environmental science, 2022)
Dielectric capacitors with a high operating temperature applied in electric vehicles, aerospace and underground exploration require dielectric materials with high temperature resistance and high energy density. Polyimide (PI) turns out to be a potential dielectric material for capacitor applications at high temperatures. In this review, the key parameters related to high temperature resistance and energy storage characteristics were introduced and recent developments in all-organic PI dielectrics and PI-matrix dielectric nanocomposites were discussed. Synthetic strategies for new functional PI via modification at the molecular level together with the design engineering of nanofillers and multilayer structures of PIs were also analysed. Finally, a systematic summary of the current challenges and future developments for capacitor materials used at high temperatures were presented. Dielectric capacitors with a high operating temperature applied in electric vehicles, aerospace and underground exploration require dielectric materials with high temperature resistance and high energy density.